BURNOUT OF SOCIAL WORKERS AT Dr. HASAN SADIKIN BANDUNG CENTRAL HOSPITAL - Radityo Bimo Kartika Aji; Meiti Subardhini; Yana Sundayani (Indonesian Journal of Social Work, 2020)
The high workload can cause burnout. Burnout makes the worker not pay attention to the person he helped, thus reducing the quality of service. The research method used is descriptive research method with qualitative approach. The informant consisted of 11 people, two medical social workers, three medical social worker partners, and six medical social worker patients. The result of the research showed that: a) medical social workers experiencing burnout with the most emerging aspect of emotional exhaustion, b) depersonalization aspects, medical social workers showed apathetically and acting callous at work, c) medical social worker feel they can't work optimally but in the reality, they have good performance based on Indeks Kinerja Individu (IKI), d) Medical social worker can keep working with good performance because of their love to the profession, e) The burnout shown by medical social workers has no effect to the helping process to the patient in Dr. Hasan Sadikin General Hospital. The main factors of burnout of medical social workers is a barrier in their career, which leads the medical social worker can't get their rights based on their performance and education.